PENGARUH LIFE STYLE TERHADAP PERILAKU KONSUMSI MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK DI UNIVERSITAS HKBP NOMMENSEN MEDAN - Geraldo, Olan; Sihombing, Natalia ET; Sinaga, Kepler (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This study aims to examine the influence of lifestyle on the consumption behavior of students at the Faculty of Social and Political Sciences, HKBP Nommensen University, Medan. Lifestyle variables were measured through three indicators: activities, interests, and opinions. This research employed a quantitative method using a survey approach, with data collected from 194 respondents selected through simple random sampling. Data analysis was conducted using instrument tests, partial test (t-test), simultaneous test (F-test), and the coefficient of determination with the assistance of SPSS software. The results show that activities, interests, and opinions have a positive and significant effect on students’ consumption behavior, both partially and simultaneously. The F-test obtained a value of 38.188 > 2.65 with a significance level of 0.000, indicating that the independent variables jointly influence consumption behavior. The Adjusted R² value of 0.371 demonstrates that the three variables explain 37.1% of the variation in consumption behavior, while the remaining 62.9% is influenced by other factors outside this study, such as economic conditions, family influence, and social media. These findings highlight that students’ lifestyle plays an important role in shaping their consumption patterns. Therefore, students are expected to manage their lifestyle wisely to avoid excessive and consumptive behavior.